REVIEW OF RECENT RESEARCH ON PENTERNARY NANOSTRUCTURED THIN FILMS - Ho, Soon Min; Ayeshamariam, A (2019)
Nowadays, thin film technology has received an enormous interest among the scientists and was used in solar cell application. Solar energy is free, renewable energy that has been employed in the world. In the past, a variety of thin films (binary, ternary and quaternary films) have been produced in order to search cheaper absorbing materials. The obtained thin films are more flexible, high conversion efficiency and less expensive if compared to silicon based solar cells. The aim of this work is to study the synthesis of penternary nanostructured thin films by using several methods as reported by different researchers from around corner of the world (Physical and chemical technique). The obtained samples such as Cu(In,Ga)(S,Se)2 and Cu2ZnSn(SSe)4 films have been characterized by using various tools. The solar cell devices show power conversion efficiency of 10 % and 12.4 % for Cu(In,Ga)(S,Se)2 and Cu2ZnSn(SSe)4 thin films, respectively